EQUILIBRIUM ADSORPTION OF METHANE ANDCARBON DIOXIDE ON 5A MOLECULAR SIEVE (Journal of Engineering, 2007)
Experimental and theoretical studies have been carried out to study the adsorption of methane and carbon dioxide on 5A molecular sieve. Adsorption equilibrium isotherms of methane and carbon dioxide are reported for the temperature range 303– 333 K and pressure up to 2.5MPa. Experimental data were obtained using a static system for gas–solid adsorption. The Langmuir adsorption equilibrium equation gavegood predictions. Adsorption of methane and carbon dioxide on 5A molecular sieve is purely physical since the isosteric heat of adsorption was found to be equal to 14.804 and 37.218 kJ mole-1 for methane and carbon dioxide, respectively.